The Relationship Between Knowledge About Reproductive Health And Personal Hygiene During Menstrual in Adolescents - Elga Selwa; Is susiloningtyas (Jurnal Maternitas Kebidanan, 2026)
Personal hygiene is an effort made to maintain a person's cleanliness and health, both physically and mentally. Common physical problems include poor personal hygiene, which can increase the risk of urinary tract infections (UTIs). During menstruation, blood and sweat from the body can stick to the vulva, making it wet. If a woman does not pay attention to hygiene at this time, humid conditions can occur. Fungi and bacteria grow in the genital area, causing itching and infection. This literature review was conducted to determine the description of adolescent personal hygiene during menstruation. The method used in making this literature review is the reference search method through Google Scholar, Pubmed, and Sinta with the keywords personal hygiene, adolescents, and menstruation and menstrual health management. Articles that provide information about Personal Hygiene. Articles selected based on full text, open access, in English and Indonesian published in the last 5 years (2021 - 2025). The results of the literature review show that there is a significant correlation between knowledge about reproductive health and adolescent personal hygiene behavior during menstruation. The study found that many adolescent girls do not know much about their reproductive health, which potentially increases the risk of infection and other health problems. Conclusion: Menstrual hygiene or personal hygiene in adolescents is still poor, so correct information is needed so that adolescents can practice good personal hygiene during menstruation